2005
DOI: 10.1001/archinte.165.13.1552
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Study of Association of Helicobacter pylori Infection With Morbid Obesity in Taiwan

Abstract: Our data indicated an inverse relationship between morbid obesity and H pylori seropositivity. These findings raise the hypothesis that a lack of H pylori infection, especially during childhood, might enhance the risk of the development of morbid obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 29 publications
5
80
1
2
Order By: Relevance
“…A second possibility is that the ready availability of food in Western culture may obliterate other effects. In East Asian populations, where most people have corpus gastritis and highly interactive strains of H. pylori, obesity has been associated with H. pylori-negativity (117). The hypothesis that modern obesity is due in part to absence of H. pylori, and that the mechanism is through disturbances in gastric hormones, remains unproven but deserves more extensive investigation.…”
Section: Absence Of H Pylori Causes Hyperghrelinemia and Reduced Gasmentioning
confidence: 99%
“…A second possibility is that the ready availability of food in Western culture may obliterate other effects. In East Asian populations, where most people have corpus gastritis and highly interactive strains of H. pylori, obesity has been associated with H. pylori-negativity (117). The hypothesis that modern obesity is due in part to absence of H. pylori, and that the mechanism is through disturbances in gastric hormones, remains unproven but deserves more extensive investigation.…”
Section: Absence Of H Pylori Causes Hyperghrelinemia and Reduced Gasmentioning
confidence: 99%
“…However, the prevalence of H. pylori infection in morbidly obese patients and its effect on ulcer progression or the response to eradication treatments is unresolved [13][14][15][16][17][18]. Furthermore, it is also unclear whether the detection and eradication of H. pylori prior to bariatric surgery can reduce the risk of postoperative peptic ulcer disease [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of present study are consistent with the report of previous studies that H. pylori infection is inversely related to obesity. For example, Wu et al [26] reported that the seropositivity of H. pylori infection was significantly lower in morbidly obese patients [25]. Furuta et al [9] have shown the body weight gain after H. pylori cure.…”
Section: Discussionmentioning
confidence: 99%